PKM Menanamkan Semangat Nasionalisme Dan Patriotisme Bagi Peserta Pemagangan Provinsi Bengkulu - Sariningsih, Marida; Imanda, Antonio; Lorita, Evi; Amin, Bando; Aprizal, Aprizal (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
This Community Service (PKM) activity was carried out by a team of lecturers and students from Dehasen University Bengkulu in collaboration with the Internship Network Communication Forum (FKJP) of Bengkulu Province. The background to this activity is the decline in the spirit of nationalism and patriotism among the younger generation due to the influence of globalization and technological developments that have shifted national values. The purpose of this activity is to re-instill the values ​​of nationalism, love of the homeland, and the spirit of defending the country to the internship participants so that they have a strong national character and social responsibility as citizens. The activity method is carried out through a participatory approach in the form of counseling, interactive discussions, and reflection on national values. The results of the activity show an increase in participants' understanding of the meaning of nationalism and patriotism and a growing motivation to practice national values ​​in everyday life. This activity contributes to the character formation of a young generation that is Pancasila-spirited, has integrity, and is ready to face global challenges without abandoning its national identity.